Elevated blood pressure is associated with higher prevalence of low visual acuity among adolescent males in Northeast China. Issue 1 (December 2017) - Zhao, Miaomiao; Wang, Wei; Yu, Han; Ma, Yunsheng; Zheng, Liqiang; Zhang, Lijuan; Wu, Guiping; Sun, Yingxian; Li, Jue
Abstract The purpose of this study is to track the trends of low visual acuity (VA) from 2005 to 2014, and to investigate its associations with systemic blood pressure (BP) components among adolescents in Northeast China. A total of 55320 students of Han nationality aged 13 to 18 years were included. There has been a significant increase in the prevalence of low VA, with 31.3% in 2005, 40.2% in 2010 and 43.4% in 2014. In multivariable-adjusted logistic regression models, each 1-mm Hg increment in systolic BP (SBP) was associated with 0.8% (95% confidence interval [CI]: 0.1–1.6%), 0.5% (95% CI: 0.1–0.9%) and 1.1% (95% CI: 0.6–1.6%) increased odds of low VA for males in 2005, 2010 and 2014; each 1-mm Hg increment in pulse pressure (PP) was associated with 1.6% (95% CI: 0.7–2.5%), 0.8% (95% CI: 0.4–1.2%) and 1.2% (95% CI: 0.7–1.7%) increased odds of low VA. Higher PP categories had greater odds for low VA compared with the reference group. Similar associations were not observed for females. We conclude that higher prevalence of low VA was significantly associated with higher SBP and PP in males. Furthermore, there was a dose-dependent association between the prevalence of low VA and the levels of PP.